Quantifying the impact of basketball performance metrics on winning in professional and collegiate basketball - Uysal, A. A.; Carroll, K.; Huebner, A.; Krush, A.; Stone, M. H. (Scientific Journal of Sport and Performance, 2026)
The aim of the investigators was to statistically analyze the relationships between basketball performance metrics and winning percentage (WIN%) in professional and collegiate basketball. Game data from 10 seasons between 2014 and 2024 were analyzed from the NBA, WNBA, NCAA, and NCAAW leagues. Basketball performance metrics included the number of possessions, points scored (PTS), three-point percentage (3P%), two-point percentage (2P%), number of free throw attempts (FTA), free throw percentage (FT%), offensive rebound percentage (OREB%), defensive rebound percentage (DREB%), turnover ratio (TOV%), assists (AST), steals (STL), blocks (BLK), personal fouls (PF), relative offensive (ORtg±) and defensive (DRtg±) ratings. Among the statistically significant relationships between WIN% and basketball performance metrics, 3P% had the strongest relationship with WIN% in NBA, whereas BLK had the strongest relationship with WIN% in WNBA and NCAA. AST had the strongest relationship with WIN% in NCAAW and was not statistically related to WIN% in NBA. The only league in which DRtg± was not statistically related to WIN% was the NBA. NBA is an offense-oriented league where creating individual scoring opportunities had a stronger impact on winning. In contrast, offensive and defensive performance showed a closer balance in their contributions to team success in the other leagues analyzed.